Analysis of Urban Sprawl Dynamics and Migration Using Geospatial Technology in Bhilwara City, Rajasthan, India - Mr. Lokesh Tripathi, Dr. Sunil Kumar (International Journal of Advanced Science and Technology, 2020)
Using Multi-spectral, Multi-date and highly spatial remote sensing satellite (MSDRSS) data has significant significance for visualisation of urban sprawl and migration. Geographic Information Systems (GIS) are a technology that makes it possible to manipulate and capture as well as to integrate with data. We want to be acquainted with and catalogue the urban sprawl on different scales such as spatial and temporal which generate an establishment for enhanced growth and sustainable management of urban centres. The city of Bhilwara has rapidly re-accelerated into a rising region after being absorbed into the urban part of the world. As the city increases in population, the need for energy causes pressure on its natural resources. Agriculture land and woodland were drained because of overpopulation and urban development. To assess the growth of urban sprawl, an urban environment in Bhilwara City was analysed by using Landsat satellite data between 2003 and 2008. As a result of this, the trade, educational, farming, and service centres of the industry were able to thrive. This is due to the fact that outdoor urban development may result in the deterioration of urban infrastructure. Migrating is just one part of the migration process. Migration occurs all over society all the time. Looking at the district level and state level numbers, we see that migration from rural to urban areas is continuing in Rajasthan. The migrants’ exposure to urbanisation and lack of land use surmounts on the rising over decades. In this article, immigration is analysed in a region where there is a lot of urban sprawl. Still more, migration is studied where it is examined at the city level. Ultimately, urban sprawl patterns and migration are studied as one aspect of the research.